1994
DOI: 10.1172/jci117595
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 beta-modulated gene expression in immortalized human chondrocytes.

Abstract: Immortalized human chondrocytes were established by transfection of primary cultures of juvenile costal chondrocytes with vectors encoding simian virus 40 large T antigen and selection in suspension culture over agarose. Stable cell lines were generated that exhibited chondrocyte morphology, continuous proliferative capacity (> 80 passages) in monolayer culture in serum-containing medium, and expression of mRNAs encoding chondrocyte-specific collagens II, IX, and XI and proteoglycans in an insulin-containing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
410
0
5

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(428 citation statements)
references
References 61 publications
13
410
0
5
Order By: Relevance
“…Nuclear run-on and transient transfection experiments have shown that a IL-1␤ negative signal for human COL2A1 gene transcription involves a 577-bp proximal promoter region and the specific enhancer sequence present in the first intron of the gene (23). Similar effects were also observed in immortalized human articular chondrocytes (24). These data suggest that IL-1␤ exerts its control on type II collagen production through binding sequences of the promoter and/or first intron regions of the COL2A1 gene.…”
mentioning
confidence: 70%
“…Nuclear run-on and transient transfection experiments have shown that a IL-1␤ negative signal for human COL2A1 gene transcription involves a 577-bp proximal promoter region and the specific enhancer sequence present in the first intron of the gene (23). Similar effects were also observed in immortalized human articular chondrocytes (24). These data suggest that IL-1␤ exerts its control on type II collagen production through binding sequences of the promoter and/or first intron regions of the COL2A1 gene.…”
mentioning
confidence: 70%
“…Human chondrocyte cell line C28/I2 was a kind gift from Dr. Mary Goldring (41). The cells were cultured in Dulbecco's modified Eagle's medium (DMEM)/Ham's F-12 (1:1) (Invitrogen), containing 5% fetal bovine serum (FBS) with 100 units/ml penicillin G and 100 g/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…The co-transfection experiments were also carried out in an immortalized human chondrocyte cell line, C-20/A4 (Figure 3, Goldring et al, 1994). Such a cell line was used because the cellular origin of chondrosarcomas are chondrocytes, thus we were interested in analysing the activity of the fusion proteins in a cellular context resembling as much as possible the one in which they occur in vivo.…”
Section: Transcriptional Activation Of Tec and Ews/tec Isoformsmentioning
confidence: 99%
“…COS-1 cells were maintained in DMEM with 10% FBS and the human chondrocyte cell line C-20/A4 (Goldring et al, 1994) in DMEM/F12 (1 : 1) with 10% FBS. Both culture medium were supplemented with 100 units/ml penicillin G, 100 mg/ml streptomycin sulfate and 0.25 mg/ml amphotericin B.…”
Section: Cell Linesmentioning
confidence: 99%